Next-Generation Anti-Angiogenic Therapies as a Future Prospect for Glioma Immunotherapy; From Bench to Bedside - Shamshiripour, Parisa; Hajiahmadi, Fahimeh; Lotfi, Shahla; Esmaeili, Niloofar Robab; Zare, Amir; Akbarpour, Mahzad; Ahmadvand, Davoud (Frontiers in Immunology, 2022)
Glioblastoma (grade IV glioma) is the most aggressive histopathological subtype of glial tumors with inordinate microvascular proliferation as one of its key pathological features. Extensive angiogenesis in the tumor microenvironment supplies oxygen and nutrients to tumoral cells; retains their survival under hypoxic conditions; and induces an immunosuppressive microenvironment. Anti-angiogenesis therapy for high grade gliomas has long been studied as an adjuvant immunotherapy strategy to overcome tumor growth. In the current review, we discussed the underlying molecular mechanisms contributing to glioblastoma aberrant angiogenesis. Further, we discussed clinical applications of monoclonal antibodies, tyrosine kinase inhibitors and aptamers as three major subgroups of anti-angiogenic immunotherapeutics and their limitations. Moreover, we reviewed clinical and preclinical applications of small interfering RNAs (siRNAs) as the next generation anti-angiogenic therapeutics and summarized their potential advantages and limitations. siRNAs may serve as next-generation anti-angiogenic therapeutics for glioma. Additionally, application of nanoparticles as a delivery vehicle could increase their selectivity and lower their off-target effects